MiR-20b-5p attenuates hypoxia-induced apoptosis in cardiomyocytes via the HIF-1α/NF-κB pathway. (8th June 2020) - Zhou, Zhongquan; Chen, Songwen; Tian, Zhiming; Deng, Shibing; Yi, Xuying; Yang, Shaning; Yang, Xuexin; Jin, Lijun; Shi, Wanqing
Abstract: Chronic hypoxia is a common inducer of end-stage cardiovascular disease. In cells under hypoxia, the hypoxia-inducible factor-1 (HIF-1) plays a vital role in regulating downstream target genes. However, the mechanism of hypoxia in cardiomyocytes is still unclear. In this study, we aimed to identify novel downstream epigenetic targets of HIF-1α in cardiomyocytes under hypoxia. H9c2 cells were exposed to hypoxia condition, and quantitative real-time PCR analysis was performed to evaluate the expression of miR-20b-5p. The results indicated that the expression of miR-20b-5p was down-regulated in H9c2 cells under low oxygen condition. Meanwhile, HIF-1α overexpression further down-regulated the miR-20b-5p expression in H9c2 cells transfected with HIF-1α plasmids. In addition, Annexin-V-FITC/PI flow cytometry analysis suggested that overexpression of miR-20b-5p attenuated cell apoptosis under hypoxia condition in H9c2 cells. Western blot analysis showed that the hypoxia apparently increased Bax and cleaved-caspase-3, but decreased Bcl-2 expression in H9c2 cells, indicating that hypoxia-induced NF-κB signaling pathway activation is mediated by miR-20b-5p. Hypoxia-induced H9c2 cell apoptosis was reduced after HIF-1α knockdown as shown by the flow cytometry analysis. In conclusion, we identified that miR-20b-5p plays an important role in mediating cardiomyocytes apoptosis under hypoxia, which is mediated by the HIF-1/NF-κB signaling pathway.